Budgetary Convergence in the WEAMU : Adjustment Through Revenue or Expenditure? - Nachega, Jean-Claude.; Dore, Ousmane (Washington, D.C. : International Monetary Fund, 2000)
A regional convergence pact adopted recently by the Conference of Heads of States of WAEMU provides a framework for fiscal convergence similar to the European Union's Maastricht Treaty. Using bivariate co-integration and error-correction models, this paper investigates the relationship between revenue and expenditure in seven member countries to determine the feasibility and nature of the policy adjustment required to meet the new convergence criteria. The results indicate that, in the long run, there is causality running from revenue to expenditure in Burkina Faso and Senegal, from expenditure to revenue in Benin and Togo, a bidirectional causality in Cote d'Ivoire and Mali, and no causality in Niger.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet